Pengaruh Gaya Komunikasi Pemimpin Terhadap Kinerja Karyawan Pada Perusahaan PT. Asuransi Mega Pratama Cabang Palembang (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2020)
This research aims to analyse the impact of leaders’ communication toward the organisations’ performance on insurance companies in Palembang. The data used in this research is a primary data that obtained from the questionnaires. The number of sample research is 54 respondents from five insurance companies in Palembang, such as PT. Asuransi Mega Pratama Palembang.The method of data collection is questionnaire with chi square analysis. The result of the research shows that there is a significant difference between the respondents with low intensity of communication and high intensity of communication to their leaders toward the employees’ performance on insurance companies in Palembang.